2008
DOI: 10.1103/physreva.77.045602
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Schrödinger equation for a superfluid Fermi gas in the BCS-BEC crossover

Abstract: We introduce a quasianalytic nonlinear Schrödinger equation with beyond mean-field corrections to describe the dynamics of a zero-temperature dilute superfluid Fermi gas in the crossover from the weak-coupling Bardeen-Cooper-Schrieffer ͑BCS͒ regime, where k F ͉a͉ Ӷ 1 with a the s-wave scattering length and k F the Fermi momentum, through the unitarity limit k F a → Ϯϱ to the Bose-Einstein condensation ͑BEC͒ regime where k F a Ͼ 0. The energy of our model is parametrized using the known asymptotic behavior in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…The total phase change throughout the soliton is determined as the difference (26) and results in the integral,…”
Section: Field Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total phase change throughout the soliton is determined as the difference (26) and results in the integral,…”
Section: Field Equationsmentioning
confidence: 99%
“…This inspires attempts to develop complementary approaches for ultracold Fermi gases exploiting only a macroscopic wave function. Prominent examples of such attempts are the modifications of the Ginzburg-Landau (GL) approach [24,25] for cold Fermi gases in the BCS-BEC crossover, and the GP and nonlinear Schrödinger equations [26]. The GL method is valid in a rather narrow temperature region close to the critical temperature T c .…”
Section: Introductionmentioning
confidence: 99%
“…In general, Bose and Fermi subsystems are described by the Lieb-Liniger and Gaudin-Yang theories, respectively. Here we are interested in weak Bose-Bose interactions (we consider small positive g b ) and attractive Fermi-Fermi interactions and the superfluid Fermi-Bose system is described by the nonlinear Schrödinger-like equation (1) [29][30][31][32][33]. In the BCS weak attractive coupling limit the fermionic subsystem coefficient is κ = 1/4, while in the molecular unitarity limit it is κ = 1/16 [26].…”
Section: Modelmentioning
confidence: 99%
“…Here we choose (α − λ) = 32/(3 √ π), β = 4πα/η with η = 22.22, α = 32ξ/(3 √ π ), and λ = 32(ξ − 1)/(3 √ π) with ξ = 1.1 [10]. The bulk chemical potential of the Fermi superfluid is expressed as [10,16,17] μ p (n p ,a f ) = 2 2 m p (6π 2 n p ) 2/3 g 2 1/3 n 1/3 p a f ,…”
Section: Modelmentioning
confidence: 99%
“…Thus the function (5) with Eq. (6) provides a smooth interpolation between the bulk chemical potential of a Fermi superfluid in the weak-coupling limit and that in the unitary limit for both the uniform case and the trapped case [10,17,18]. It was shown that the results with the choice of the fitting parameters δ = 20π/(3π 2 ) 2/3 , k = δ/(1 − ζ ), and ζ = 0.44 [10] agreed well with the corresponding Monte Carlo data [23,24].…”
Section: Modelmentioning
confidence: 99%